14a+14b+6c+2c-2b-6a=

Simple and best practice solution for 14a+14b+6c+2c-2b-6a= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14a+14b+6c+2c-2b-6a= equation:


Simplifying
14a + 14b + 6c + 2c + -2b + -6a = 0

Reorder the terms:
14a + -6a + 14b + -2b + 6c + 2c = 0

Combine like terms: 14a + -6a = 8a
8a + 14b + -2b + 6c + 2c = 0

Combine like terms: 14b + -2b = 12b
8a + 12b + 6c + 2c = 0

Combine like terms: 6c + 2c = 8c
8a + 12b + 8c = 0

Solving
8a + 12b + 8c = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-12b' to each side of the equation.
8a + 12b + -12b + 8c = 0 + -12b

Combine like terms: 12b + -12b = 0
8a + 0 + 8c = 0 + -12b
8a + 8c = 0 + -12b
Remove the zero:
8a + 8c = -12b

Add '-8c' to each side of the equation.
8a + 8c + -8c = -12b + -8c

Combine like terms: 8c + -8c = 0
8a + 0 = -12b + -8c
8a = -12b + -8c

Divide each side by '8'.
a = -1.5b + -1c

Simplifying
a = -1.5b + -1c

See similar equations:

| (n+5)*5=55 | | 7-x^2=4x | | a=-5+4b | | -6-3x=9-8x(1dp) | | 13p+19q+p-5q-5p= | | -6-3x=9-8x | | 5x(2x-1)-(2x-1)=0 | | 2k^2-3k-1=0 | | 2a-9=-5 | | 2(x+8)=6x-4 | | 4x+2.14x=3.49x | | 10m+6n-2m+9n= | | 2x^2+10x=9 | | 7+4x=7x+7 | | -8(2b+3)+(17b-9)=0 | | 6x^2-66x+36=0 | | 2d+11e+9d+7e= | | 3X^7+6X^6-9X^5+6X^4= | | axb=-15 | | 9b+7b= | | ab=-15 | | 2x+3(x-5)=4x+18 | | 6x-10=2x+8 | | 4x^2+20x-48=0 | | 7a-a-a= | | 6y-2=10 | | d+e+e+d+d+e+d= | | 5x-1=4x | | 10x-6=94 | | (5a+14b-9c-8)(6)= | | 6x+2=44 | | 3x^2-10x-5=3x(1-x) |

Equations solver categories